TOPICAL PROBLEMS OF PEDAGOGY: HOW THESE CHANGE IN DIGITAL ENVIRONMENTS - Žogla, Irēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Digital technologies have brought about crucial educational changes that gained inexperienced scope. The article attends theoretical sources and introduces analysis of the most crucial changes in the science of pedagogy that might help explorers focus on the topical problems of pedagogy. Researchers have written extensively about the paradigm change in education in the digital era and have long understood that meaningful activities define effective educator and student decisions. Alongside with these, the characteristics of the problems of pedagogical science have obtained new appearances and require new investigation: the changes introduced by digital technologies have gained rapid global-wide dimensions and challenge adequate analysis; students and even experienced researchers find it difficult to distinguish between significant problems and their appearances in mobile environments; competencies’ approach in education also delivers new unknowns while the quality of graduates do not demonstrate the appropriate capability at their work places; holistic approach to the learner balanced development in the digital environment is seldom addressed. The article synthesizes the most common pedagogical problems triggered by the difusion of digital technologies in educational environment with the aim to highlight these and therefore shape or refine the scientific method of reaserch in pedagogy.